Ca(2+)-activated non-selective cation current in rabbit ventricular myocytes - Wu, Yuejin (Blackwell Science Inc, 2000)
1. Oscillatory currents (OCs) were studied in isolated rabbit ventricular myocytes with whole cell mode voltage clamp using Na(+)-free intracellular and extracellular solutions under conditions where K(+) currents were anticipated to be eliminated or minimized. 2. All OCs were dependent on release of Ca(2+) from the sarcoplasmic reticulum (SR) because they were associated with intracellular Ca(2+) ([Ca(2+)](i)) transients, and were suppressed by high concentrations of BAPTA (20 mmol l(−1)) or pretreatment with the SR antagonist agents ryanodine (10 μmol l(−1)) or thapsigargin (1 μmol l(−1)). 3. The reversal potential (V(rev)) for OCs shifted with changes in the calculated V(rev) for Cl(−) (E(Cl)) but was between E(Cl) and the calculated V(rev) for elemental monovalent cations (E(Cat)), indicating that more than one Ca(2+)-activated current contributed to OCs. 4. Addition of the Ca(2+)-activated Cl(−) current (I(Cl(Ca))) antagonist, niflumic acid, shifted the OC V(rev) to E(Cat), suggesting that I(Cl(Ca)) and a Ca(2+)-activated non-selective cation current (I(CAN)) contributed to the observed OCs. 5. A reduced niflumic acid-insensitive Ca(2+)-activated OC persisted following marked symmetrical reduction of Cl(−) in the intracellular and extracellular solutions. Subsequent removal of all extracellular monovalent cations, by N-methyl-D-glucamine (NMDG) substitution, eliminated OCs and the inward holding current suggesting that I(CAN) and I(Cl(Ca)) accounted for all or most of the Ca(2+)-activated OC in the absence of Na(+). 6. The OC V(rev) was equal to E(Cl) in the absence of monovalent elemental cations. Under these conditions niflumic acid eliminated all OCs. 7. Macroscopic OC is partially due to I(CAN) in rabbit ventricular myocytes.